Risk Factors of Congenital Anomalies in South Sumatera Indonesia - Ziske Maritska; Theofilus Aswadi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Abstract Introduction. Congenital anomaly is one of the leading causes of neonatal death. It is the third leading cause of neonatal death in Indonesia. More than half of all congenital anomalies can’t be related to a specific cause, suggesting multiple risk factors. This study aims to identify patterns and risk factors of congenital anomalies in RSUP Dr. Mohammad Hoesin Palembang. Methods. This observational descriptive study with a cross-sectional design used 100 patients’ medical records, taken at RSUP Dr. Mohammad Hoesin Palembang, as samples. Missing data were complemented with a phone interview. Samples were picked using a proportional random sampling method. Collected data were counted within each category of congenital anomalies. Results. There were 366 neonatal patients diagnosed with congenital anomalies at RSUP Dr. Mohammad Hoesin Palembang in 2015. The most prevalent (44,8%) congenital anomalies belonged to congenital anomalies of the digestive system, followed by congenital anomalies of the circulatory system (18,6%), and cleft lip/palate (11,5%). Following risk factors were found: the history of maternal active or passive smoking (41%), maternal exposure to chemicals or solvents (31%), family member with congenital anomalies of the same category (27%), maternal drug consumption (26%), maternal infection (22%), maternal diabetes mellitus (4%), and maternal hypertension (4%). Conclusion. History of maternal active or passive smoking was the most frequently found risk factors among patients of congenital anomalies.